Ceramic material suspending agent

By using the combination of high -molecular suspension and natural polymer suspension in ceramic slurry, combined with appropriate PH adjustment, the problem of poor stability of ceramic slurry has been solved, and the improvement of suspended dispersing performance and adhesion is realized. Swing forming of taste ore and solid waste raw materials.

CN119371214APending Publication Date: 2025-01-28WUHAN HUANGHELOU FLAVOR & SPICES
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411382346.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The prior art is difficult to effectively improve the stability of ceramic slurries, especially when low-grade ore and solid waste raw materials are used, resulting in poor suspension stability and difficult grouting and molding.

Method used

Provide a ceramic material suspension, including polymer suspension, natural polymer suspending agent and distilled water. It is fully mixed with mixed mixing to prepare a slurry suspension, and the ammonia water is adjusted during ball milling Diversified performance and adhesion.

Benefits of technology

It significantly improves the stability of ceramic slurry, avoids the phenomenon of secretion of water, and ensures the stability and efficiency of the slurry in the process of grouting. It has high economic and environmental benefits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119371214A_ABST
    Figure CN119371214A_ABST
Patent Text Reader

Abstract

The invention discloses a ceramic material suspending agent which comprises the following raw materials in parts by weight: 2-3 parts of welan gum, 9-3 parts of konjac gum, 6-2 parts of polyvinyl alcohol and 983-992 parts of distilled water. The invention provides a slurry suspending agent aiming at barren ceramic raw materials, which is beneficial to the stability of slurry and avoids bleeding and sedimentation phenomena. The method can be used for barren solid waste raw materials and low-grade ceramic raw materials, is stable in performance, and has relatively high economic and environmental benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramic material suspension agents, in particular to a special suspension agent generally applicable to barren ceramic raw materials. Background Art

[0002] In recent years, my country's ceramic industry has developed rapidly, which has led to an increase in the consumption of natural mineral raw materials for ceramics, especially non-renewable mineral resources. In order to achieve sustainable development, the ceramic industry urgently needs to find new ceramic raw materials to replace natural minerals. At present, strengthening the comprehensive utilization of low-grade ores, co-existing ores, refractory ores and tailings, and encouraging building materials companies to use solid wastes such as tailings and industrial waste as ceramic admixtures are important research directions for sustainable development.

[0003] The mineral components of low-grade ores, tailings and industrial waste slag usually include feldspar and quartz, which are barren raw materials. This makes the hydration ability of raw material particles poor during the preparation of mud, resulting in poor suspension stability of the mud system and difficulty in slip casting. The stability of ceramic slurry is mainly affected by Brownian motion, as well as the coagulation interference of particles in the slurry and the control of the stability mechanism between particles (such as steric stabilization mechanism, electrostatic stabilization mechanism and electrostatic steric stabilization mechanism). Summary of the invention

[0004] Based on the above deficiencies in the prior art, the technical problem solved by the present invention is to provide a special suspending agent that is generally applicable to various barren ceramic raw materials, which can significantly improve the stability of ceramic slurry and meet the needs of using low-grade raw materials and solid waste to prepare complex-shaped ceramics by grouting molding. The present invention is conducive to the slurry to achieve stability, and no more water seepage and sedimentation will occur. The invention can be used for barren solid waste raw materials and low-grade ceramic raw materials, has stable performance, and has high economic and environmental benefits.

[0005] In order to solve the above technical problems, the present invention provides a ceramic material suspension agent, a ceramic slurry suspension agent, comprising the following raw materials in parts by weight: 4 to 9 parts of a synthetic polymer suspension agent, 3 to 9 parts of a natural polymer suspension agent and 983 to 992 parts of distilled water.

[0006] As a preferred embodiment of the above technical solution, the ceramic material suspension provided by the present invention further includes part or all of the following technical features:

[0007] As an improvement of the above technical solution, the natural polymer suspending agent is at least one of gelatin, gum arabic, xanthan gum, guar gum, konjac gum, and pectin, and the synthetic polymer suspending agent is at least one of polyvinyl alcohol, polyacrylic acid, Wenlun gum, and sodium polyacrylate.

[0008] As an improvement of the above technical solution, the ceramic slurry suspending agent may also contain 10 to 50 parts by weight of an inorganic suspending agent, 10 to 20 parts by weight of a surfactant, and 1 to 10 parts by weight of a dispersant.

[0009] As an improvement of the above technical solution, the inorganic suspending agent is at least one of bentonite, kaolin, silicon dioxide, and calcium carbonate, the surfactant is polyoxyethylene ester, and the dispersant is sodium tripolyphosphate.

[0010] As an improvement of the above technical solution, the ceramic slurry suspension comprises the following raw materials in parts by weight: 2 to 3 parts of Wenlun gum, 9 to 3 parts of konjac gum, 2 to 6 parts of polyvinyl alcohol and 983 to 992 parts of distilled water.

[0011] As an improvement of the above technical solution, the surfaces of the Wenlun gum and konjac gum have hydrophilic groups, and the slurry is stabilized through solvation and spatial stabilization mechanism. The Wenlun gum can also improve the Zeta potential of the slurry particle surface, and further stabilize the slurry using the spatial stabilization mechanism.

[0012] As an improvement of the above technical solution, the ceramic slurry suspending agent is used for ceramic slurry, and the raw materials of the ceramic slurry are iron tailings, fly ash and waste glass powder.

[0013] As an improvement of the above technical solution, the ceramic slurry is passed through an 80-mesh sieve.

[0014] As an improvement of the above technical solution, the method for preparing the ceramic slurry suspension is to stir and mix thoroughly for 6 hours to prepare the slurry suspension.

[0015] As an improvement of the above technical solution, the dosage of the suspending agent is 0.3% of the mass of the ceramic slurry.

[0016] As an improvement of the above technical solution, the ceramic material suspension agent and the ceramic slurry are mixed and then ammonia water is added to adjust the pH value to 9 to 11.5.

[0017] As an improvement of the above technical solution, after the ceramic material suspension agent and the ceramic slurry are mixed, ammonia water is added to adjust the pH value to 10, which is optimal.

[0018] The purpose of selecting a suitable pH is to adjust the viscosity of the slurry so that the slurry can fully fill the gypsum mold during the grouting process.

[0019] The present invention studies the Zeta potential of the slurry at different pH values ​​and finds that the absolute value of the Zeta potential increases with the increase of the pH value. When the pH value is 10, the Zeta potential of the slurry can reach -33.6V. At the same time, the effect of pH at 9 to 11.5 on the viscosity of the slurry is studied. It is found that as the pH value of the slurry increases, the viscosity first decreases and then increases, and the viscosity is the smallest when the pH value is 10. A pH of 10 can ensure a suitable Zeta potential while the slurry has good fluidity.

[0020] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:

[0021] The suspending agent in the present invention ensures the suspension and dispersion performance of the slurry, has good adhesion, and is easy to promote and use.

[0022] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present invention more obvious and easy to understand, the following is a detailed description in combination with the preferred embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the technical solution of the embodiment of the present invention, the drawings of the embodiment are briefly introduced below.

[0024] Figure 1 (a) is a graph showing a 48-hour sedimentation test of a ceramic material suspension prepared in Example 1 of the present invention added to a ceramic slurry;

[0025] Figure 1 (b) is a graph showing a 48-hour sedimentation test of a ceramic material suspension prepared in Example 2 of the present invention added to a ceramic slurry.

[0026] Figure 1 (c) is a graph showing a 48-hour sedimentation test of a ceramic material suspension prepared in Comparative Example 1 of the present invention added to a ceramic slurry.

[0027] Figure 1 (d) is a graph showing a 48-hour sedimentation test of a ceramic material suspension prepared in comparative example 2 of the present invention added to a ceramic slurry.

[0028] Figure 1 (e) is a graph showing a 48-hour sedimentation experiment in which the ceramic material suspension prepared in comparative example 3 of the present invention was added to ceramic slurry. DETAILED DESCRIPTION

[0029] The specific implementation modes of the present invention are described in detail below, which is a part of this specification. The principles of the present invention are explained through examples. Other aspects, features and advantages of the present invention will become clear through the detailed description.

[0030] The present invention designs a slurry suspension agent for ceramic barren raw materials. The materials used in the slurry suspension agent in the embodiments and comparative examples are: A: one or more of Wenlun gum, konjac gum, polyvinyl alcohol, and hydroxypropyl methylcellulose, and B: distilled water. The raw materials of the ceramic slurry are iron tailings, fly ash, and waste glass powder. A small amount of ammonia water is added to adjust the pH of the slurry.

[0031] Example 1

[0032] (1) According to the weight ratio: 2 parts of Wenlun glue, 6 parts of konjac glue, 6 parts of polyvinyl alcohol, and 986 parts of distilled water are weighed.

[0033] (2) The mixture was thoroughly mixed by magnetic stirring for 6 hours to prepare a slurry suspension.

[0034] (3) The ceramic slurry raw materials were weighed according to the proportion, placed in a nylon ball mill, and ball milled using a planetary ball mill. The ball milling speed was 500 revolutions per minute, and the mixing time was 6 hours. The powder was taken out and passed through an 80-mesh sieve to prepare a mixed material.

[0035] (3) The raw materials of ceramic slurry are one or more of barren materials such as tailings and fly ash. The ceramic raw materials and pure water are weighed (ceramic slurry solid content is 55wt%), put into a nylon ball mill, and ball milled using a planetary ball mill. The ball milling speed is 500 revolutions per minute, and the mixing time is 6 hours. After taking out the powder, pass it through an 80-mesh sieve to prepare a mixed material.

[0036] (4) Mix the slurry suspending agent and the mixed material, and the amount of the suspending agent is 0.3% of the slurry mass. Add ammonia water to adjust the pH value to 10, put it into a nylon ball mill, and use a planetary ball mill to prepare a slurry at a speed of 500 rpm for 540 minutes. The viscosity of the ceramic slurry is 760mPas. The Zeta potential is -46.2mV. After the ceramic slurry is poured into a 10ml measuring cylinder and subjected to a 48h sedimentation test, the slurry does not show stratification.

[0037] Example 2

[0038] (1) According to the weight ratio: 3 parts of Wenlun glue, 3 parts of konjac glue, 4 parts of polyvinyl alcohol, and 990 parts of distilled water are weighed.

[0039] (2) The mixture was thoroughly mixed by magnetic stirring for 6 hours to prepare a slurry suspension.

[0040] (3) The raw materials of ceramic slurry are one or more of barren materials such as tailings and fly ash. The ceramic raw materials and pure water are weighed (ceramic slurry solid content is 55wt%), put into a nylon ball mill, and ball milled using a planetary ball mill. The ball milling speed is 500 revolutions per minute, and the mixing time is 6 hours. After taking out the powder, pass it through an 80-mesh sieve to prepare a mixed material.

[0041] (4) Mix the slurry suspending agent and the mixed material, and the amount of the suspending agent is 0.3% of the slurry mass. Put it into a nylon ball mill, use a planetary ball mill, and prepare a slurry at a speed of 500 rpm for 540 minutes. The viscosity of the ceramic slurry is 778mPas. The Zeta potential is -50.4mV. After the ceramic slurry is poured into a 10ml measuring cylinder and subjected to a 48h sedimentation test, the slurry does not show stratification.

[0042] Comparative Example 1

[0043] (1) According to parts by weight: 0 part of Wenlun glue, 0 part of konjac glue, and 1000 parts of distilled water are weighed.

[0044] (2) The mixture was thoroughly mixed by magnetic stirring for 6 hours to prepare a slurry suspension.

[0045] (3) The raw materials of ceramic slurry are one or more of barren materials such as tailings and fly ash. The ceramic raw materials and pure water are weighed (ceramic slurry solid content is 55wt%), put into a nylon ball mill, and ball milled using a planetary ball mill. The ball milling speed is 500 revolutions per minute, and the mixing time is 6 hours. After taking out the powder, pass it through an 80-mesh sieve to prepare a mixed material.

[0046] (4) Mix the slurry suspending agent and the mixed material, and the amount of the suspending agent is 0.3% of the slurry mass. Put it into a nylon ball mill, use a planetary ball mill, and prepare a slurry at a speed of 500 rpm for 540 minutes. The viscosity of the ceramic slurry is 289mPas. The Zeta potential is -5.6mV. After the ceramic slurry is poured into a 10ml measuring cylinder and subjected to a 48h sedimentation experiment, a supernatant liquid appears in the slurry, and the height is 1.8ml.

[0047] Comparative Example 2

[0048] (1) According to parts by weight: 0 part of Wenlun glue, 9 parts of konjac glue, and 991 parts of distilled water are weighed.

[0049] (2) The mixture was thoroughly mixed by magnetic stirring for 6 hours to prepare a slurry suspension.

[0050] (3) The raw materials of ceramic slurry are one or more of barren materials such as tailings and fly ash. The ceramic raw materials and pure water are weighed (ceramic slurry solid content is 55wt%), put into a nylon ball mill, and ball milled using a planetary ball mill. The ball milling speed is 500 revolutions per minute, and the mixing time is 6 hours. After taking out the powder, pass it through an 80-mesh sieve to prepare a mixed material.

[0051] (4) Mix the slurry suspending agent and the mixed material, and the amount of the suspending agent is 0.3% of the slurry mass. Put it into a nylon ball mill, use a planetary ball mill, and prepare the slurry at a speed of 500 rpm for 540 minutes. The viscosity of the ceramic slurry is 958mPas. The Zeta potential is -34.2mV. After the ceramic slurry is poured into a 10ml measuring cylinder and subjected to a 48h sedimentation experiment, a supernatant liquid appears in the slurry with a height of 0.2ml.

[0052] Comparative Example 3

[0053] (1) According to the weight ratio: 1 part of hydroxypropyl methylcellulose and 999 parts of distilled water are weighed.

[0054] (2) The mixture was thoroughly mixed by magnetic stirring for 6 hours to prepare a slurry suspension.

[0055] (3) The raw materials of ceramic slurry are one or more of barren materials such as tailings and fly ash. The ceramic raw materials and pure water are weighed (ceramic slurry solid content is 55wt%), put into a nylon ball mill, and ball milled using a planetary ball mill. The ball milling speed is 500 revolutions per minute, and the mixing time is 6 hours. After taking out the powder, pass it through an 80-mesh sieve to prepare a mixed material.

[0056] (4) Mix the slurry suspending agent and the mixed material, and the amount of the suspending agent is 0.3% of the slurry mass. Put it into a nylon ball mill and use a planetary ball mill to prepare a slurry at a speed of 500 rpm. The viscosity of the ceramic slurry is 387mPas. The Zeta potential is -15.4mV. After the ceramic slurry is poured into a 10ml measuring cylinder and subjected to a 48h sedimentation experiment, the slurry is divided into three layers from top to bottom. The top layer has a foam layer, the middle layer is a clear liquid, and the bottom layer is a reward sedimentation layer. The height between the clear liquid and the top layer is 2ml.

[0057] The raw materials listed in the present invention, as well as the upper and lower limits and interval values ​​of the raw materials of the present invention, and the upper and lower limits and interval values ​​of the process parameters (such as temperature, time, etc.) can all realize the present invention, and the embodiments are not listed one by one here.

[0058] The above is only a preferred embodiment of the present invention, which certainly cannot be used to limit the scope of rights of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and changes can be made without departing from the principle of the present invention, and these improvements and changes are also regarded as the protection scope of the present invention.

Claims

1. A ceramic material suspension, characterized in that: The ceramic slurry suspension agent comprises the following raw materials in parts by weight: 4~9 parts of synthetic polymer suspending agent, 9~3 parts of natural polymer suspending agent and 983~992 parts of distilled water.

2. The ceramic material suspension according to claim 1, characterized in that: The natural polymer suspending agent is at least one of gelatin, gum arabic, xanthan gum, guar gum, konjac gum and pectin, and the synthetic polymer suspending agent is at least one of polyvinyl alcohol, polyacrylic acid, vinblastine and sodium polyacrylate.

3. The ceramic material suspension according to claim 1, characterized in that: The ceramic slurry suspension agent may further include 10 to 50 parts by weight of an inorganic suspension agent, 10 to 20 parts by weight of a surfactant, and 1 to 10 parts by weight of a dispersant.

4. The ceramic material suspension according to claim 3, characterized in that: The inorganic suspending agent is at least one of bentonite, kaolin, silicon dioxide and calcium carbonate, the surfactant is polyoxyethylene ester, and the dispersant is sodium tripolyphosphate.

5. The ceramic material suspension according to claim 1, characterized in that: The ceramic slurry suspending agent comprises the following raw materials in parts by weight: 2-3 parts of Wenlun glue, 3-9 parts of konjac glue, 2-6 parts of polyvinyl alcohol and 983-992 parts of distilled water; the ceramic slurry suspending agent is used for ceramic slurry, and the raw materials of ceramic slurry are iron tailings, fly ash and waste glass powder.

6. The ceramic material suspension according to claim 5, characterized in that: The ceramic slurry is passed through an 80-mesh sieve.

7. The ceramic material suspension according to claim 1, characterized in that: The method for preparing the ceramic slurry suspension is to stir and fully mix for 6 hours to prepare the slurry suspension.

8. The ceramic material suspension according to claim 1, characterized in that: The amount of the suspending agent is 0.3% of the mass of the ceramic slurry.

9. The ceramic material suspension according to claim 1, characterized in that: After the ceramic material suspension agent and the ceramic slurry are mixed, ammonia water is added to adjust the pH value to 9-11.

5.

10. The ceramic material suspension according to claim 1, characterized in that: After the ceramic material suspension agent and the ceramic slurry are mixed, ammonia water is added to adjust the pH value to 10.

Citation Information

Patent Citations

  • Aorthite micro-nano pore heat insulation refractory material and preparation method thereof

    CN114133229A

  • Ceramic tile prime slurry based on magnesium aluminate spinel and preparation method thereof

    CN116947511A